1991
DOI: 10.1128/mcb.11.12.6067
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of p53 mutants for transcriptional activity.

Abstract: The wild-type p53 protein functions to suppress

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(84 citation statements)
references
References 33 publications
4
80
0
Order By: Relevance
“…One tumour with a shifted band on exon 6 was unavailable for sequence, and although improbable, in this case we cannot exclude a silent polymorphism at codon 213 since the tumour was positively stained with anti-p53 antibody. We cannot speculate if every mutation encountered has the same prognostic value since each mutation alters the p53 conformation differently, leading to different biological properties and tumorigenic potential (Halevy et al, 1990;Raycroft et al, 1991;Mukhopadhyay & Roth, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…One tumour with a shifted band on exon 6 was unavailable for sequence, and although improbable, in this case we cannot exclude a silent polymorphism at codon 213 since the tumour was positively stained with anti-p53 antibody. We cannot speculate if every mutation encountered has the same prognostic value since each mutation alters the p53 conformation differently, leading to different biological properties and tumorigenic potential (Halevy et al, 1990;Raycroft et al, 1991;Mukhopadhyay & Roth, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The protein expressed by pMSV val135 contains an A to V change at amino acid 135, has a temperaturesensitive phenotype and is in a mutant conformation at 378C . Previous studies have indicated that at the non-permissive temperature, this mutant is defective for transcriptional activation (Raycroft et al, 1991;Jackson et al, 1995). No promoter activation was observed using the pMSV control vector.…”
Section: Distal and Proximal P53-binding Sites Permit Synergistic Tramentioning
confidence: 99%
“…In vitro studies have shown that this p53 mutant binds poorly to a consensus DNA sequence recognized by wt p53 (Kern et al, 1991), and lacks wt p53 transactivation activity (Raycroft et al, 1991). Therefore, if it is functioning at the transcriptional level, it may regulate dierent target genes (Chen et al, 1992).…”
Section: Transduced P21mentioning
confidence: 99%